Oxidative Damage Compromises Energy Metabolism in the Axonal Degeneration Mouse Model of X-Adrenoleukodystrophy - Galino, Jorge (Mary Ann Liebert, Inc., 2011)
AIMS: Chronic metabolic impairment and oxidative stress are associated with the pathogenesis of axonal dysfunction in a growing number of neurodegenerative conditions. To investigate the intertwining of both noxious factors, we have chosen the mouse model of adrenoleukodystrophy (X-ALD), which exhibits axonal degeneration in spinal cords and motor disability. The disease is caused by loss of function of the ABCD1 transporter, involved in the import and degradation of very long-chain fatty acids (VLCFA) in peroxisomes. Oxidative stress due to VLCFA excess appears early in the neurodegenerative cascade. RESULTS: In this study, we demonstrate by redox proteomics that oxidative damage to proteins specifically affects five key enzymes of glycolysis and TCA (Tricarboxylic acid) cycle in spinal cords of Abcd1(−) mice and pyruvate kinase in human X-ALD fibroblasts. We also show that NADH and ATP levels are significantly diminished in these samples, together with decrease of pyruvate kinase activities and GSH levels, and increase of NADPH. INNOVATION: Treating Abcd1(−) mice with the antioxidants N-acetylcysteine and α-lipoic acid (LA) prevents protein oxidation; preserves NADH, NADPH, ATP, and GSH levels; and normalizes pyruvate kinase activity, which implies that oxidative stress provoked by VLCFA results in bioenergetic dysfunction, at a presymptomatic stage. CONCLUSION: Our results provide mechanistic insight into the beneficial effects of antioxidants and enhance the rationale for translation into clinical trials for X-adrenoleukodystrophy. Antioxid. Redox Signal. 15, 2095–2107.